THE INFLUENCE OF APPLICATION LEARNING MODELS BY INTERACTIVE CONCEPTUAL INSTRUCTION (ICI) BASED ON LEARNING RESULTS INFORMATION AND COMMUNICATION TECHNOLOGY IN VIII GRADE STUDENT OF SMPN 6 SINGARAJA - Ngurah Alit Suryawan (Universitas Pendidikan Ganesha, 2012)
The purpose of this study was to (1) knowing about the influence of application learning models by interactive conceptual instruction (ICI) based on learning results information and communication technology in VIII grade student of SMPN 6 Singaraja and (2) knowing the student respond about the influence of application learning models by interactive conceptual instruction (ICI) based on learning results information and communication technology in VIII grade student of SMPN 6 Singaraja.The type of this study is apparent experimental research study design used by Posttest-Only Control Group Design. The population of this study was the VIII grade student of SMPN 6 Singaraja in odd semester academic year 2011/2011 sample of this study using student of VIII b1 grade as a exsperimental group and VIII B4 grade as a control group with the total number of students are 66 people. The end of the lesson both sample classes given a trial skill tests (psychomotor) and multiple-choice tests (cognitive) using the same instrument. Before the cognitive question were used for the test, it has been analyzed using the analysis of qualitative and quantitative. The data collection which mine done by multiple-choice test method for one correct answer is used for the cognitive measure, and psychomotor test to measure the domain of psychomotor skills. Test method was performed to obtain the final value after the data were treated in the experimental group and control group. Prior to analysis test conducted prerequisites that includes a test for normality and homogeneity test. Then analyzed the data using the ttest. While for the response using the the questionnaire method.Based on the results of tests of normality and homogeneity of the test result data from the two groups, obtained the data sample are both normal and homogeneous. The test of hypotesis used t-test. The results of calculations obtained t-observed = 3,088091 while the value of t-table = 1,99773, so t-observed > t-table so Ho rejected and Ha be accepted. While as many 6% of students responded very positively, 67% of students responded positively, 27% of students responded quite positively. Thus, it can be concluded that there is a significant influence on the application of learning models interactive conceptual instruction (ICI) based on learning results information and communication technology in VIII grade student of SMPN 6 Singaraja.